Estudo, considerações e dificuldades na análise não-linear de estruturas de concreto armado através do método dos elementos finitos - Janaina Soraia de Sa Machado (2000)
In the last few years a numer of finite element constitutive models for reinforced concrete have been proposed in order to correclly describe the behaviour of this material These models try to incorporate aspects such as tensile cracking, crushing, strain softening, concrete steel interaction, tension stiffening, amongst others. Morreover, the success of the widely used linear structural analyses and of the monlinear analyses for steel structures and the advancement of strucutral analysis software have encouraged the development of nonlinear study of reinforced concrete structures to obtain solutions to be used in practical applications. This work present some procedures those that want to investigate the reinforced concrete strucutres using commercial available finite element software must undertake. Initially it shows various constitutive possibilities to model the reinforced concrete behaviour and the numerical aspects that evolve the nonlinear analysis. Some examples are presented and comparisons are made in order to determine a model that best suits behaviour expected in this class of material.Numerical difficulties encountered during tlhe solution of the nonlinear equations and the choice (and adjustment) of tlhe controlling parameters for the models are emphasised. The results of the analyses are more an indication that the models need to be improved than practical application that it could offert at this stage.